2017
DOI: 10.1007/s00381-017-3441-y
|View full text |Cite
|
Sign up to set email alerts
|

Fetal ventriculomegaly: Diagnosis, treatment, and future directions

Abstract: Fetal ventriculomegaly (VM) refers to the enlargement of the cerebral ventricles in utero. It is associated with the postnatal diagnosis of hydrocephalus. VM is clinically diagnosed on ultrasound and is defined as an atrial diameter greater than 10 mm. Because of the anatomic detailed seen with advanced imaging, VM is often further characterized by fetal magnetic resonance imaging (MRI). Fetal VM is a heterogeneous condition with various etiologies and a wide range of neurodevelopmental outcomes. These outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 66 publications
1
54
0
3
Order By: Relevance
“…The accuracy of fetal ultrasound reported in the literature differs enormously. The overall accuracy of ultrasound when compared to autopsy is around 77%, while for separate underlying causes accuracy can be as low as 30% and as high as 100% [2,[11][12][13][14][15][16][17][18][19]. The reported variation in accuracy rates is due to the heterogeneity of the underlying causes discussed in these papers, from acquired infections to genetic predispositions and disruptions in various brain structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy of fetal ultrasound reported in the literature differs enormously. The overall accuracy of ultrasound when compared to autopsy is around 77%, while for separate underlying causes accuracy can be as low as 30% and as high as 100% [2,[11][12][13][14][15][16][17][18][19]. The reported variation in accuracy rates is due to the heterogeneity of the underlying causes discussed in these papers, from acquired infections to genetic predispositions and disruptions in various brain structures.…”
Section: Discussionmentioning
confidence: 99%
“…In case of VM, which is an ultrasound sign rather than a disease in itself, diagnosis of underlying pathology in utero is challenging both before and after 24 weeks' GA. Counseling on the prognosis of VM prior to 24 weeks' gestation is hampered by the fact that progressive dilatation in the third trimester cannot reliably be predicted, while this is the only significant predictor for postnatal major brain abnormalities in cases of isolated VM. [2,14,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other CNS anomalies included the following: VMG, defined by a ventricular diameter greater than 10 mm, in six cases (100%) and short corpus callosum, defined smaller than the fifth percentile, in three cases.…”
Section: Resultsmentioning
confidence: 99%
“…al. [14] revealed that head circumference (HC) remains normal in most cases of VM. Only in cases with severe hydrocephaly causing abnormal intracranial pressure, resulting in increased head circumference (HC) above 400 mm, may qualify for elective caesarean section due to the high risk of obstetrical complications; however, there were no such cases in our study group.…”
Section: Discussionmentioning
confidence: 99%